The Influence of Financial Literacy and Financial Behavior on the Financial Performance of SMEs: A Regression Analysis Study in Indonesia - Yuszak Mahya (Eduvest - Journal of Universal Studies, 2024)
The method used in this research is the regression analysis method with the variables used, namely Financial Literacy (X1), Financial Behavior (X2) on Financial Performance (Y). This research uses quantitative methods and uses a sample of 118 respondents who are SME owners spread throughout Indonesia. The research uses SPSS software to assist in data processing. From the results of this research it can be concluded that the t test results obtained a significant value for the financial literacy variable of 0.019 and a regression coefficient value of 0.209. The significance value <0.05 and the positive regression coefficient value indicate that financial literacy has a positive effect on financial performance . The results of the t test obtained a significant value for the financial behavior variable of 0.005 and a regression coefficient value of 0.200. The significance value <0.05 and the positive regression coefficient value indicate that financial behavior has a positive effect on financial performance. These findings also show that financial literacy has a positive effect on the performance of SMEs and financial behavior has a positive effect on the financial performance of SMEs in Indonesia